Finansowanie inwestycji jednostek samorządu terytorialnego w Polsce - Cecur, Agata (Financing Investments of Local Government Units in Poland, 2009)
The demographic development and the progressing urbanization, then suburbanization led to the increase of infrastructure needs though the fundamental enlarging of functional urban areas. The completion of investment in the scope of local technical infrastructure is a prolonged process due to technical as well as economic factors. Therefore, the completion of investments requires financing the determining roots. Poland's access to the European Union was one of more important events of the last years. This fact influenced the change in investment conditions in the country. This significantly broadened the possibilities for financing new investments due to new resources coming from budget of this organization. The expenditure on investment activity became the most legible sign for the local resourcefulness and the innovation.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 29-38